Prevalence and coexistence of KRAS, BRAF, PIK3CA, NRAS, TP53, and APC mutations in Indian colorectal cancer patients: Next-generation sequencing–based cohort study. Issue 2 (February 2017) - Jauhri, Mayank; Bhatnagar, Akanksha; Gupta, Satish; BP, Manasa; Minhas, Sachin; Shokeen, Yogender; Aggarwal, Shyam
Colorectal cancer incidences are on a rise in India. In this study, we have analyzed the mutation frequencies of six potential biomarkers, their coexistence, association with clinicopathological characteristics, and tumor location in Indian colorectal cancer patients. Next-generation sequencing was performed to identify mutations in the six potential biomarker genes using formalin-fixed paraffin-embedded tissue blocks of 112 colorectal cancer patients. The mutation frequency observed in KRAS, BRAF, PIK3CA, NRAS, TP53, and APC was 35.7%, 7.1%, 16.1%, 6.3%, 39.3%, and 29.5%, respectively. The significant associations of mutations were KRAS with age less than 60 years (p = 0.041), PIK3CA with males (p = 0.032), tumor stage I–II (p = 0.013), lack of metastasis in lymph nodes (p = 0.040), NRAS with rectum (p = 0.002), and APC with T2 stage of tumor growth (p = 0.013). No single patient harbored mutations in these six genes or any five genes simultaneously. Significance was noted in coexistence of KRAS with APC (p = 0.024) and mutual exclusion of KRAS with BRAF (p = 0.029). PIK3CA exon 9 was observed to be more frequently associated with KRAS mutations than PIK3CA exon 20 (p = 0.072). NRAS mutations were mutually exclusive with BRAF and PIK3CA mutations. As per our knowledge, this is the first next-generation sequencing–based biomarker study in Indian colorectal cancer patients. Frequent coexistence of gene mutations in pairs and triplets suggests that synergistic effect of overlapping mutations might further trigger the disease. In addition, infrequent coexistence of multiple gene mutations hints toward different signaling pathways for colorectal cancer tumorigenesis.